The Impacts of Employee Mental Health in The Workplace: A Literature Review - Ananda Fortunisa (Journal of International Conference Proceedings (JICP), 2022)
Previous research has described a lot about how to manage the mental health of employees in the workplace. However, there is no comprehensive understanding the impact of the role of employee mental health on work learning systems, participatory practices, gratitude and employee emotions. The purpose of this study was to examine the impact of employee mental health. The research method is by reviewing 50 articles selected and screened based on key findings. This research reveals that mental health and gratitude are understood in a variety of ways. Mental health is primarily defined as mental health experiences and responses, and workplace learning primarily refers to learning through participatory practices. In addition, this study describes the relationship between mental health and learning in the workplace. Most studies focus on the active role of mental health in supporting and/or hindering learning in the workplace. Some research shows mental health in the workplace is negatively affected by gratitude. This research also reveals that mental health affects employees' emotions at work. This study suggests that companies can maintain their employees’ mental health through various human resource management strategies, and for further research, it is recommended to describe trends and gaps in this field.